Managerial valuation of applicant credentials and personal traits in hiring decisions - James R. Jones; Catherine Y. Co; James K. Harter; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2011)
We study how managers value applicant credentials and personal traits in hiring decisions. Using the ordered probit model, we confirm previous results - managers rank applicant traits higher than credentials. However, we also uncover patterns not previously observed - managerial valuations of some of these characteristics are dependent on managers' perception of the overall state of the economy, on firm and immediate workplace characteristics, and on managers' personal characteristics. Manager valuations of credentials vary with a large number of factors; this is not so for applicant personal traits. This is not surprising as most managers view the five traits considered as extremely important.
urn:nbn:de:101:1-201105173204
Keywords: J29; M12; C21; 330; hiring practices; credentials; personality; ordered probit